5 - ICT Utilisation and Associated barriers in Teaching among Middle-level Academics in Nigerian Universities - Oyefara, John Lekan; Adejoh, Pius; Adisa, Waziri B.; Abdulsalam, Khadeejah A.; Alabi, Tunde (Journal of Higher Education in Africa, 2022)
This article seeks to understand the barriers to information and com- munications technology (ICT) utilisation among middle-level academics in Nigerian universities. It makes use of a cross-sectional survey and key informant interviews to interrogate the problem. A total of 1,325 middle- level lecturers drawn from 12 South-western Nigerian universities took part in the study. Because of the nature and character of the Nigerian state and the historical contexts of its higher education, the political economy approach was adopted along with ICT utilisation resistance theory to explain barriers to ICT utilisation in Nigerian universities. The article finds that there is a significant relationship between the availability, utilisation and quality of teaching in Nigerian universities. Specifically, it finds that in universities where lecturers had tablets they were 1.5 times more likely to deliver quality teaching. It also finds that in universities where lecturers used multimedia projectors, students were 2.7 times more likely to receive quality teaching. On the barriers to ICT utilisation, the article finds that lack of funding, lack of strong institutional policy and support infrastructure such as broadband internet connectivity and constant electricity supply are among the major constraints to ICT-based higher education. It therefore suggests the development of a comprehensive policy on ICT-based education and massive investment in university education in Nigeria.